PENGARUH STRUKTUR AKTIVA, MANAGERIAL OWNERSHIP, FIRM SIZE, DAN LEVERAGE TERHADAP FIRM PERFORMANCE - Vanessa, Marshiella; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to understand how asset structure, management ownership, company size and leverage affect the company kinerjance of a manufacturing company listed on the Indonesian stock exchange during the period 2018-2020. The sample is drawn by targeted sampling method, and the valid data is 75 companies. Data processing techniques using eviews 12 and Microsoft Excel 2016. The findings of this study show that asset structure, senior management ownership, firm size and leverage have a significant impact on firm kinerjance.